1999
DOI: 10.1007/s004290050286
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of long- and short-range signalling during early tendon development

Abstract: Tendons connect muscle to skeletal elements. Although tendons have been shown to originate from the lateral plate mesoderm, very little is known at the molecular level about how they are formed. We have found that two genes, Follistatin and Eph-A4, are expressed in regions associated with tendon formation in developing chick limbs. Follistatin is expressed near the tip of the digits and subsequently around the tendon, whereas Eph A4 transcripts were localized in a slightly more proximal region and later in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…More robust markers of tenocytes include Scleraxis (SCX), Tenomodulin (TNMD), Tenascin-C (TNC), Cartilage oligomeric matrix protein (COMP), and Thrombospondin-4 (THBS4), which are not only collectively expressed in tendons, but individually also present in other tissue types. [22][23][24][25][26] Developmental studies have also implicated genes such as Six1/2, Eph-A4, Eya1/2, Egr1/2, and Mohawk (Mkx), 25,[27][28][29][30] although it has not been established whether these genes show temporally restricted expression in tendon tissue.…”
Section: Discussionmentioning
confidence: 99%
“…More robust markers of tenocytes include Scleraxis (SCX), Tenomodulin (TNMD), Tenascin-C (TNC), Cartilage oligomeric matrix protein (COMP), and Thrombospondin-4 (THBS4), which are not only collectively expressed in tendons, but individually also present in other tissue types. [22][23][24][25][26] Developmental studies have also implicated genes such as Six1/2, Eph-A4, Eya1/2, Egr1/2, and Mohawk (Mkx), 25,[27][28][29][30] although it has not been established whether these genes show temporally restricted expression in tendon tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Because we have not analyzed all BMPs, antagonists, and receptors, it is possible other factors within the BMP signaling system play important roles that would change our perception. Our choice of genes was governed by our previous finding of effects of exogenous GDFs and the fact that follistatin is expressed around the forming tendon in chicken embryos, where exogenous follistatin inhibits tendon formation [4]. BMPR1b was chosen because it is known to interact with GDF-5, which does not bind to BMPR1a [13].…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains reports (sometimes anecdotal) that genes are located in tendons during embryonic limb development. The tyrosine kinase receptor, Eph-A4 (Patel et al, 1996;D'Souza and Patel, 1999), the transforming growth fac- (Hurle et al, 1989;Birk and Mayne, 1997), mouse (Niederreither et al, 1995), human (Waggett et al, 1998) E12 death due to vascular defects (Lohler et al, 1984) Type III collagen Chick (Birk and Mayne, 1997), mouse (Niederreither et al, 1995) Abnormal type I collagen fibrillogenesis (Liu et al, 1997) Type V collagen Chick (Birk and Mayne, 1997), mouse (Imamura et al, 2000) Abnormal type I collagen fibrillogenesis (Andrikopoulos et al, 1995) Type VI collagen Chick (Ros et al, 1995), mouse (Watanabe et al, 1997).…”
Section: Molecular Markers Of Tendons During Embryonic Developmentmentioning
confidence: 99%
“…Chick (D'Souza and Patel, 1999) E9 death (Winnier et al, 1995) Fgf8 Chick (Edom-Vovard et al, 2001a) Early death (Meyers et al, 1998) Fgf18 Chick (Ohuchi et al, 2000) Bone phenotype (Ohbayashi et al, 2002;Liu et al, 2002) Follistatin Chick (D'Souza andPatel, 1999) Multiple defects and perinatal death (Matzuk et al, 1995) Tgf␤2 Chick (Merino et al, 1998) and mouse (Pelton et al, 1989) Widespread defects including vascular but tendon not reported (Dunker and Krieglstein, 2000) Transmembrane proteins…”
Section: Bmp4mentioning
confidence: 99%
See 1 more Smart Citation